Measuring Institutional Maturity as an Approach for Successful Implementation of the Strategy in Public Organizations «An Analytical Vision» - Mohamed, Abdelrahim (The Arab Journal of Administration, 2025)
The concept of institutional maturity is one of the concepts that organizations have taken care of in recent years, especially with interest in strategic plans. Although the concept has historical roots, but with the great development and competition between organizations to achieve institutional excellence, thinking and searching for a methodology to achieve its goals. Hence, the orientation and interest in institutional maturity. The philosophy of maturity is based on that the maturity of the organization is not linked to its age in the market, but there are other requirements that help it to quickly achieve and maintain maturity. The study started from a major problem, which is to what extent there is maturity in the current organizations? Do these organizations have the requirements to achieve it? The importance of the study is due to knowing the ability of organizations to achieve institutional maturity, the study aimed to reach a vision for the application of institutional maturity, and reached a number of results, including that the issue of institutional maturity is not applied in Arab organizations, but is applied in some Western organizations. The study recommended the application of the proposed vision to apply Institutional maturity that came in this study.